Seed storage influences the seedling emergence and growth of Tocoyena formosa, a native species from Brazilian Savannah? - Bonamigo, Thaliny; Masetto, Tathiana Elisa; Scalon, Silvana de Paula Quintão (Iheringia, Série Botânica., 2024)
Studies related to seed performance during storage represent a start for the sustainable use of native plant species, such as Tocoyena formosa, a native species from the Brazilian savannah with antifungal and anti-inflammatory properties. This study aimed to verify the effects of packaging, temperature, and storage period on the seeds of Tocoyena formosa. The seeds were packed in aluminum foil and glass bottles and stored at 5 °C, 15 °C and 25 ± 2 °C for 0, 14, 28, and 56 days. After, the seeds were sowed in cell trays containing substrate composed of pine bark chips, aggregating agents, vermiculite, coconut fiber, and mineral complements at 70% shade; seedlings quality was evaluated until complete stabilization of emergence. The fresh seeds had a lower percentage (42%) of emergence than the seeds stored for 56 days, which presented 57% emergence regardless of the temperature or packaging. The stored seeds in impermeable glass packaging at and temperature range of 5 to 15 °C showed higher emergence in less time and provided seedlings of high quality.